Tax Avoidance and Stock Returns: The Moderating Effect of Independent Commissioners - Thitania Chatrine Junaidi; Rino Tam Cahyadi; Lalu Rahmat Sohdi (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to analyze the effect of tax avoidance on stock returns and to examine the role of independent commissioners as a moderating variable in this relationship. The object of this research focuses on consumer goods companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. This quantitative study utilized a sample of 10 companies with a total of 50 observations, which were analyzed using panel data regression and Moderated Regression Analysis (MRA) with the Common Effect Model (CEM) approach. Tax avoidance is proxied by the Effective Tax Rate (ETR), alongside control variables including profitability (ROA), leverage (DER), and firm size. The empirical results prove that tax avoidance has a positive and significant effect on stock returns, indicating that the market responds positively to tax efficiency as it effectively increases shareholder profit. However, independent commissioners are unable to moderate the relationship between tax avoidance and stock returns. In conclusion, investors in this particular sector tend to focus more on the company's fundamental performance rather than the effectiveness of internal corporate governance oversight.